Antibacterial activities and characteristics of some marine fungi strains isolated from Co To beach, Quang Ninh province - Le Thi, Hong Minh; Nguyen, Mai Anh; Vu, Thi Quyen; Phi , Thi Dao; Tran , Van Hieu; Doan Thi, Mai Huong; Pham, Van Cuong; Vu Thi, Thu Huyen (Vietnam Journal of Marine Science and Technology, 2023)
Resistance to pathogenic bacteria may lead to serious health problems. Scientists found that discovering novel antimicrobial compounds is possible by exploring rarely investigated environments. Therefore, this work focused on isolating and identifying some fungal strains collected from the Co To sea. We tested whether such strains can produce compounds with vital activities, including antibacterial and antifungal. The antimicrobial activity of the marine fungi crude extracts was performed by the Bioassay method in a 96-well tray. The minimum inhibitory concentration (MIC) test results showed that 22 strains of marine fungi from samples with different geographic coordinates and 20/22 strains had antibacterial activity against at least two strains of microorganisms tested. The biological evaluation revealed that strains M257 and M238 inhibited 4 to 5 tested strains with MIC values equal to or lower than positive controls. Using a BLAST analysis in the GenBank database, morphological comparisons of the two selected candidate strains with similar known species and phylogenetic analyses were conducted on the 18S rRNA gene regions, and maximum likelihood revealed that M257 belongs to Talaromyces genus, and M238 belongs to Aspergillus penicillioides. The isolates were analyzed in a phylogenetic tree based on MegaX software.